Answer:
Yes, -x - 3y = -1 is the same as y = -1/3x - 1/3
Step-by-step explanation:
-x - 3y = -1
Add x to both sides which gives you
-3y = x-1
Divide both sides by -3 which gives you
y = -1/3x-1/3
Reminder whatever you do to one side you have to do to the other side!
Hope this helps!
No. 1 = x
No. 2 = 2x+7
No. 3 = x-12
Answer:
x+(2x+7)+(x-12) = 131
From there you solve to get the numbers:
34, 75 and 22
Answer:
118x
Step-by-step explanation: hopes this helps
Answer
A) C=5+2d
Step-by-step-explanation
Answer:
The pair (0,3) is not a solution to the equation
Step-by-step explanation:
This can be proved by simply replacing the x and y variables in the equation by the x and y values of the pair, and checking if the equation renders a true statement:
By replacing x and y with their values in the pair (0,3), that is x=0 and y=3, in the equation y = 5 - 2x we get:
3 = 5 - 2 (0)
3 = 5 - 0
3 = 5
which is NOT a true statement.
On the other hand, the other two pairs (2,1) and (1,3) render true statements:
1 = 5 - 2 (2)
1 = 5 - 4
1 = 1
and
3 = 5 - 2 (1)
3 = 5 - 2
3 = 3